Dhanalakshmi Srinivasan College of Arts and Science for Women - A Special Issue: Life Sciences-Microbiology - Sowmiya, K. (International Journal of Life Science and Pharma Research, 2021)
This special Issue is to create collections of Articles on specific topics. The aim is to build a community of authors and readers to discuss the latest research and develop new ideas and research directions.The articles in this issue are led by Editors who are experts in the subject and oversee the editorial process for papers.This provide a great platform to promote the break through research works.The potentially advanced special issue focussing on biomedical application from branches of life science, Chemistry andPhysics . This special issue is a join collaboration between Dhanalakshimi srinivasan College of Arts & Science for women Autonomous & International journal of Life Science & Pharma Research. This Provide a platform for the researchers to publish their innovative research findings.It was discussed Antibacterial ,Antifungal, Anticancer, Antioxidant and Anticonventional activities..It also included papers on phytochemical screening and pharmaceutical activity of medicinal plants andalso focused on biosynthesis of Nanomaterials and its Biological applications.The papers in this special issue broadly divided into the applications of Microbiology, Biotechnology,Biochemistry ,Chemistry and Physics.